Pola Komunikasi Orang Tua Terhadap Anak Usia Dini (AUD) di Karangjati Sinduadi RT 17 Rw 41 Kec. Mlati Kab.Sleman - Agung Kaisar Siregar (BUHUTS AL-ATHFAL: Jurnal Pendidikan dan Anak Usia Dini, 2021)
This study aims to see how the communication patterns of parents to early childhood (AUD) in Karangjati Sinduadi RT 17 RW 41, Mlati District, Sleman Regency. This research is a qualitative research with a field study approach, a case study type. Sources of data obtained from this study are the words or actions of the interviewee and the observations related to this research.Based on the results of the study, it was found that initially the communication patterns of parents to early childhood were not good due to the different backgrounds of parents, and after the authors conducted research and observations and the authors provided a good and correct method of communication patterns to residents or parents, thank God the communication patterns Parents have started well, parents have implemented good communication patterns towards their families especially towards their children, namely: democratic or open communication patterns, then Laissez-Faire communication patterns.The next finding is that the character of early childhood has improved, children seem to have started to open up to their parents, after parents apply good and correct communication patterns to their children, then the children also look more familiar with their father and mother, and children have started telling stories often. to the father and mother about children's activities outside the home, either at school or playing with friends.